HOUSEHOLD CHOICE OF DIARRHEA TREATMENTS FOR CHILDREN UNDER THE AGE OF FIVE IN KENYA: EVIDENCE FROM THE KENYA DEMOGRAPHIC AND HEALTH SURVEY 2008-09 - Njeri, Grace; Muriithi, Moses (European Scientific Journal, ESJ, 2013)
This study investigated the factors that influence the household choice of treatments for children suffering from diarrhea in Kenya using a multinomial logit approach. A sample of 771 under-5 children was drawn from the 2008/2009 Kenya Demographic and Health Survey. It was found that 29.86 percent of the children were not administered with any sort of treatment for their diarrhea. It was surprising to note that only 4 of the affected children were given zinc supplements. The study found that prior knowledge/experience of oral rehydration salts, mother’s education level, place of residence, household wealth and birth spacing were key factors determining the use of recommended treatments for childhood diarrhea. Given the inadequate and low usage of ORT and zinc respectively, the study recommends strengthening awareness on childhood diarrhea and the recommended treatments that can be used to manage it as well as increasing the availability and accessibility of zinc supplements.